Measuring the corporate brand image of Islamic banking institutions - Ab Hamid, Siti Ngayesah; Wan Jusoh, Wan Jamaliah; Maulan, Suharni (Faculty of Management, UTM Johor Bahru, 2018)
The measurement of image in the banking sector is important especially to understand customer’s perception towards the bank service. However, the available scales measuring the image of banks are mainly based on the conventional institutions, which neglect the important Islamic values adopted by Islamic bank. As such, this study proposes to develop a reliable and valid scale to measure the functional component of the corporate brand image for Islamic banking institutions. Based on the available literatures and interviews with relevant stakeholders, a modified scale is suggested. The result of EFA and CFA shows that the functional image of an Islamic brand could be divided into four dimensions which are contact personnel, shariah advisory panel, access to service, and service offerings. The results provide a tool that could be used by banking management to measure the bank image.